Strategic determinants of market orientation since the pandemic: a scoping review (2023)
A scoping review is presented whose objective is to analyze the strategic determinants of the concept of market orientation from the beginning of the Covid-19 pandemic. 60 specialized articles were taken as reference, published in databases such as Scielo, Dialnet, Scopus and repositories of indexed journals in Colombia, considering the previous theoretical elements exposed at the end of the 20th century. The results present the existence of three categories of analysis related to digital marketing, consumer and branding and the objective of durability. The conclusions reveal that the market orientation aims to evolve towards the personalized exploration of the needs of users and consumers, from the effective management of information focused on the possibility of organizational reinvention, adaptation to change and the constant application of the sense of innovation.